Comparison of different wind turbines under various seismic and wind loading - Altuğ, Yavuz. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2017., 2017)
The energy sector can be broadly classiﬁed into two main groups that are non renewable sources and renewable sources. One of the most preferred types of renewable energy for investment is wind energy in consequence of technological improvements on wind energy sector. Making investment is a complex process since it involves economic and technical requirements. This thesis represents technical and economic feasibility of the wind farms. Selection of the site is the ﬁrst step to be taken for the wind turbine projects. Three places, C¸anakkale, Balıkesir and Kayseri, were speciﬁed as extremely suitable for making investment. For technical consideration, soil uncertainty was anal ysed from the viewpoint of soil stiﬀness that is represented by the subgrade reaction of modulus. Soil uncertainty is a signiﬁcant issue in the design stage since the stiﬀ ness of the soil has an impact on the system natural frequency. Additionally, ultimate bearing capacity of soil was calculated by using Terzaghi’s Bearing Capacity Theory to prevent any failure in soil. In the thesis, two diﬀerent wind turbines models were used whose rated powers are 1.80 MW and 3.45 MW. The behaviours of the systems were investigated in terms of overturning moment, base shear and period values obtained from SAP 2000. Finally, strength checks were done according to the standards of API by checking buckling, bending, and shear stresses of the system. All the analyses were carried out to ﬁnd the optimum value of design variables, which are the wall thickness of tower, dimension of foundation and tower diameter. For economical consideration, the ﬁnancial models were created to manage cash ﬂows throughout the lifetime of the projects. When all the alternatives are taking into consideration, one of the most sig niﬁcant ﬁndings of this study is that making wind turbine investment is advantageous compared to the acquisition of interest income in bank accounts.
Keywords: Wind turbines.; Wind energy conversion systems.